Victim compensation policy and white‐collar crime: public preferences in a national willingness‐to‐pay survey - Galvin, Miranda A. (Criminology & public policy, 2018)
We use survey data from a nationally representative sample to explore public support for taxpayer‐funded victim compensation programs for financial fraud, consumer fraud, identity theft, and burglary. We use contingent valuation (willingness‐to‐pay) methodology to infer preferences for compensation programs and explore predictors of those preferences. Overall, our findings reveal that the public strongly supports the implementation of victim compensation programs. Our results also indicate, however, that this support may be driven in part by perceptions of benefiting from this program directly in the future. Additionally, a small but notable minority of respondents exhibit preferences for programs without compensation.